2014
DOI: 10.1073/pnas.1417717111
|View full text |Cite
|
Sign up to set email alerts
|

An engineered affibody molecule with pH-dependent binding to FcRn mediates extended circulatory half-life of a fusion protein

Abstract: Significance One of the central questions in biopharmaceutical development is how to extend circulation residence times of protein-based drugs to improve efficacy and patient comfort. Immunoglobulin G and serum albumin are rescued from lysosomal degradation by the pH-dependent binding to the neonatal Fc receptor and consequently have naturally long circulation half-lives. Here we describe the development and characterization of small affinity proteins (affibody molecules) that can hitchhike on the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…More recently, Seijsing et al selected affibody molecules, a 3-helix bundle scaffold protein derived from staphylococcal protein A (Figure 6f), that exhibit pH-dependent binding to the FcRn 152 . The selected affibody variants (Z FcRn ) bind human FcRn with low nanomolar affinity at pH 6 (10–50 nM), and weaker, yet functional binding at pH 7.4 (~ 100 – 1000 nM).…”
Section: 5 Alternative Strategies That Target Fcrnmentioning
confidence: 99%
“…More recently, Seijsing et al selected affibody molecules, a 3-helix bundle scaffold protein derived from staphylococcal protein A (Figure 6f), that exhibit pH-dependent binding to the FcRn 152 . The selected affibody variants (Z FcRn ) bind human FcRn with low nanomolar affinity at pH 6 (10–50 nM), and weaker, yet functional binding at pH 7.4 (~ 100 – 1000 nM).…”
Section: 5 Alternative Strategies That Target Fcrnmentioning
confidence: 99%
“…43 (Andersen et al, 2014(Andersen et al, , 2013Capon et al, 1989;Dall'Acqua et al, 2006;Elzoghby et al, 2012;Gadkar et al, 2015;Ghetie et al, 1996;Gong et al, 2011;Medesan et al, 1997;Mezo et al, 2008;Moreland, 1998;Sebak et al, 2010;Seijsing et al, 2014;Sleep et al, 2013;Sockolosky and Szoka, 2015;Ying et al, 2013;Zalevsky et al, 2010) Inhibition of the FcRn-IgG interaction Increased degradation rate of endogenous IgG in the serum. (DeLano et al, 2000;Feng et al, 2013;Foss et al, 2015;Jaggi et al, 2007;Li et al, 2005;Linker, 1983;Liu et al, 2007;Ober et al, 2004a;Raghavan et al, 1994;Roopenian and Akilesh, 2007;Sockolosky et al, 2014;Sockolosky and Szoka, 2015;Strauch et al, 2014;Swiercz et al, 2014;Vaccaro et al, 2005;Zülfikar and Koç, 2014) Fc-fusion for vaccination and pathogen neutralization (a) Use of Fc-fused to model antigens.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, disruption of this molecular complex in cynomolgus monkeys led to increased catabolic rates for IgG and, consequently, to temporarily reduced levels of IgG in the serum, with no alteration in the serum albumin levels (Mezo et al, 2008). Additionally, several C H 2, C H 3 and Fc domains were recently developed by the Dimitrov's research group (Gong et al, 2011;Ying et al, 2013), and Seijsing proposed the attachment of affibody molecules to recombinant proteins, already engineered for increased half-life (Seijsing et al, 2014). Still, as the use of these ligands is yet very limited, and their therapeutic impact is not completely determined, thus we invite the reader to consider the research papers described elsewhere (Andersen et al, 2013;Gadkar et al, 2015;Gong et al, 2011;Seijsing et al, 2014;Ying et al, 2013), which explore the role of these low molecular weight binding ligands and their utility in drug delivery or disease therapy.…”
mentioning
confidence: 99%
“…Ying et al reported a short FcRn binding motif derived from Fc CH3 domain that exhibited improved FcRn binding [33]. Seijsing et al described a detailed study using an Affibody library to screen for small affinity proteins (consisting of only 58 amino acids) [34]. Sockolosky et al used a short peptide sequence that could compete with human IgG for FcRn [35].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies had used the FcRn binding domains from SA or IgG and made fusion proteins containing these domains to achieve recycling and circulation extension [29][30][31][32], there had been also some efforts made to improve drugs' circulation properties by engineering or developing new peptide or protein binding domains of FcRn [33][34][35][36][37][38][39][40][41][42][43]. But most of these attempts including Fc-fusion proteins could not match the endogenous IgGs' long circulation half-life.…”
Section: Introductionmentioning
confidence: 99%